2021
DOI: 10.1177/15593258211016237
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Low to Moderate Doses of Ionizing Radiation Induces A Reduction of Pro-Inflammatory Ly6chigh Monocytes and a U-Curved Response of T Cells in APOE -/- Mice

Abstract: Low dose ionizing radiation (LDIR) is known to have a protective effect on atherosclerosis in rodent studies, but how it impacts different cells types involved in lesion formation remains incompletely understood. We investigated the immunomodulatory response of different doses and dose-rates of irradiation in ApoE-/- mice. Mice were exposed to external γ rays at very low (1.4 mGy.h-1) or low (50 mGy.h-1) dose-rates, with cumulative doses spanning 50 to 1000 mGy. Flow cytometry of circulating cells revealed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Furthermore, these studies ( 98 , 99 ) showed a decrease in inflammatory parameters following exposure to low-dose IR, such as reduced plaque content of CD68+ foam cells and a shift in aortic mRNA expression favoring anti-inflammatory cytokines over pro-inflammatory ones ( 98 , 99 ). These findings support the notion that IR affects the immune system, with high doses promoting inflammation ( 100 ) and pro-inflammatory macrophages ( 101 ), while lower doses lead to decreased inflammation ( 102 ). In a study by Rey et al, the immunomodulatory response to different doses of low-dose IR was investigated.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, these studies ( 98 , 99 ) showed a decrease in inflammatory parameters following exposure to low-dose IR, such as reduced plaque content of CD68+ foam cells and a shift in aortic mRNA expression favoring anti-inflammatory cytokines over pro-inflammatory ones ( 98 , 99 ). These findings support the notion that IR affects the immune system, with high doses promoting inflammation ( 100 ) and pro-inflammatory macrophages ( 101 ), while lower doses lead to decreased inflammation ( 102 ). In a study by Rey et al, the immunomodulatory response to different doses of low-dose IR was investigated.…”
Section: Discussionsupporting
confidence: 85%
“…Rey et al have shown a decrease in proinflammatory Ly6CH monocytes [351], and Edin et al (2015) have shown an activation of TGF-β3 at LDRIR [381].…”
Section: Low Dose-rate Effectsmentioning
confidence: 99%
“…Whole-body LDIR on metastatic mouse models induced anti-tumor responses via alterations of the immunosuppressive tumor environment, leading to a reduction of proinflammatory Ly6chigh monocytes in APOE−/−mice [350,351]. LDIR was upregulating selected immune components INF-γ, IL-4, and Il-5, and cytokines released stimulated CD4+ cell T-cells [274].…”
Section: Immune and Anti-tumor Ldir Effectsmentioning
confidence: 99%
“…Rey et al . [ 12 ] have shown that in Apoe -/- mice, chronic low-dose and low-dose-rate irradiation induced a switch towards an anti-inflammatory and anti-oxidative phenotype. In contrast, Mancuso et al .…”
Section: Introductionmentioning
confidence: 99%